PENENTUAN JENIS PRODUK HUKUM DALAM PELAKSANAAN PUTUSAN MAHKAMAH AGUNG TENTANG HAK UJI MATERIL (Kajian Terhadap Tindak Lanjut Putusan Mahkamah Agung 28 P/HUM/2018) - Ramadhan, Febriansyah; Efendi, Sunarto; Rafiqi, Ilham Dwi (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2022)
This study examines the problem of determining the type of legal product from the implementation of the judicial review decision, as in Supreme Court Decision 28 P/HUM/2018. The research method used is normative research, with a statutory and conceptual approach. The results of the discussion are, firstly, there are dissimilarities in forming bodies and types of legal products in the object of testing and implementing decisions. The types of legal products tested are classified as primary legislation that is compiled involving 2 powers (DPRD and the Regent), while the follow-up uses legal products that are classified as subordinate legislation that is formed solely by the Regent. Second, the Regent's Regulation that follows up has no validity, because the Regent is not authorized to independently formulate general and local norms, which do not have a juridical basis in national regulations. The follow-up must use a level product, namely Regional Regulations.